A new eccentric resonance matching layer with anti-reflection characteristics for underwater acoustic scattering suppression. (29th December 2020) - Duan, Jinxiu; Li, Shande; Wu, Xiaoxun; Wang, Cun; Ma, Yane
Abstract: The narrow frequency bandwidth and the effective frequency which cannot be low enough are two major challenges in underwater acoustics. To overcome these drawbacks, a new eccentric resonance matching layer with anti-reflection characteristics is proposed for underwater acoustic scattering suppression. Homogenization method and anti-reflection theory are applied for the design of anti-reflection structure. The complete mathematical model is developed based on the finite element method (FEM). Numerical simulations are carried out by COMSOL to verify the accuracy of the mathematical model. The results show that the proposed matching layer can significantly improve the broadband absorption capacity and can effectively suppress underwater acoustic scattering, especially at relatively low frequencies. It is a breakthrough in underwater low-frequency acoustic absorption, indicating that the structure has application prospects in underwater acoustic stealth, acoustic energy dissipation and acoustic wave regulation.